Z socjologią na Ty… Czyli jak królowa nauk potrafi wiązać ludzkie życiorysy .......... 15 - Porębski, Andrzej (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
ENGAGING WITH SOCIOLOGY: HOW THE QUEEN OF SCIENCES INTERTWINES LIFE PATHS This memoir-style article reflects on the longstanding professional and academic relationship between Prof. Tadeusz Paleczny and the author, spanning nearly five decades. Their connection began during their sociology studies and continued through collaborative work in various academic institutions, including the Polonia Research Institute, the Institute of Regional Studies, and ultimately, the Institute of Intercultural Studies.